Small-cell neuroendocrine carcinoma of the urinary bladder: A case report - Masood, Basit (Int J Health Sci (Qassim), 2020)
Primary neuroendocrine carcinomas of the urinary bladder are rare. A 60-year-old male presented with gross hematuria for the past 3 months. Diagnostic flexible cystoscopy revealed a papillary lesion above the right ureteric orifice. Transurethral resection of bladder tumor was performed and resected tissue was sent for histopathology that revealed high-grade urothelial carcinoma with small-cell neuroendocrine differentiation. Lamina propria, muscularis propria, and perineural invasion was seen which was later also confirmed by immunohistochemistry. The patient received neoadjuvant four cycles of chemotherapy and then underwent radical cystoprostatectomy with ileal conduit. The patient’s recovery was uneventful and he is on regular follow-up from the past 12 months without any disease recurrence. Early detection and aggressive management can improve the survival and prognosis of these patients.